Identification and assessment of ecotoxicological hazards attributable to pollutants in urban wet weather discharges. Issue 9 (10th July 2017) - Gosset, Antoine; Durrieu, Claude; Orias, Frédéric; Bayard, Rémy; Perrodin, Yves
Abstract : This study provides reliable insights concerning the hazards of pollutants in urban wet weather discharges that may contaminate suburban aquatic ecosystems. Abstract : Urbanization has led to considerable pressure on urban/suburban aquatic ecosystems. Urban Wet Weather Discharges (UWWD) during rainfall events are a major source of pollutants leached onto and into urban surfaces and sewers, which in turn affect aquatic ecosystems. We assessed the ecotoxicity of the different compounds identified in UWWD and identified the hazard represented by each of them. To this end, hazard quotient (HQ) values were calculated for each compound detected in UWWD based on their predicted no effect concentration (PNEC) values and their maximum measured effluent concentrations (MECmax ) found in the dissolved part of UWWD. For the 207 compounds identified in UWWD, sufficient data existed for 165 of them to calculate their PNEC. The ecotoxicity of these compounds varied greatly. Pesticides represented a high proportion of the wide variety of hazardous compounds whose HQ values were calculated (94 HQ values), and they were among the most hazardous pollutants (HQ > 1000) transported by stormwater. The hazard of combined sewer overflows (CSO) was linked mainly to heavy metals and pharmaceutical compounds. Consequently, the monitoring of these pollutants should be a priority in the future. The hazard level of certain pollutants could have been underestimated due to their adsorption onto particles, leading to their low concentration in the dissolved phase of UWWD. Hence, an in-depth study of these pollutants will be required to clarify their effects on aquatic organisms.